KEDUDUKAN PEREMPUAN DALAM NOVEL BUNGA KARYA KORRIE LAYUN RAMPAN (KAJIAN FEMINISME) - Yudianti Herawati (Kantor Bahasa Kalimantan Timur, 2017)
The purpose of this study was to describe the position of female characters in Bunga by Korrie Layun Rampan . It focused on the role and characteristics of female characters, both traditional and modern women in Bunga . This research used descriptive-qualitative method and feminism theory . In addition, it applied descriptive analysis techniques to describe the data . Analytical technique is used to determine the meaning of the story content of the research object . The results of this study illustrated that the position of women in Bunga was elevated: (1) Bunga was an objective and realistic figure of inland woman who behaved according to customs, (2) as the daughter of male village elder, Bunga personally did not rely on her parents’ status, and (3) Bunga represented a future-oriented person .